Ligiran a storybook for children ages 8-10 about the history and significance of the Pagoda Festival in Bocaue, Bulacan - Tadeo, Rommel Bartolome
The Pagoda Festival in Bocaue, Bulacan is one of the 627 folk festivals (Francisco/PhilStar, 2014) in the country. It is celebrated every first or second Sunday of July and serves as a commemoration of Jesus Christ in the form of the Mahal na Poon ng krus sa Wawa relic and the veneration of its miracles, as a thanksgiving to the blessings of water (Mariano;2017), and as a celebration of the Bocaue community and its history associated with the relic (German; 1992, 2017). The festival also exhibited the communal values by the Bocaue community such as bayanihan (during the foundation of the festivity and throughout the festival's history, heroism and resilience (as it survived and rose from the Pagoda Tragedy in 1993. This festival may serve as a noble example for the youth to learn about the importance of Filipino culture, history and moral values. However, there are multiple points of interest on this matter, based on the visual communicator's research: (1) on the learning about the Bocaue Pagoda Festival, it was evaluated that the learning of this specific festivity is underappreciated in schools, as the Bocaue schoolchildren themselves are lacking knowledge about the festival's history, plus the less-to-none prioritization of the conducted schools in Bocaue in teaching the children about the said festivity, although such lesson is mandated through the localization of subject topics in Araling Panlipunan, according to DepEd's K-12 Curriculum (DepEd, 2016); and (2) the available visual communication materials, and academic or educational references about the Bocaue Pagoda Festival available to the public are lacking, obsolete, out of circulation and especially, not child-friendly; and stated by teachers involved in the research that most of them rely on either improvising of teaching materials, or just briefly teaching it (or just mentioning it) to students due to teaching restrictions, lack of information and time constraints. The other visual materials available were only promotional ads for the purpose of annual promotion of the said festivity rather than focusing on the educational aspect of it. This research has led the visual communicator to create a project proposal for the youth with the creation of an illustrated chapter book and an exhibit for children ages 8-10 that teaches the significance of Bocaue Pagoda Festival in its various levels (historical, cultural, and moral).